Tailoring the Functional Properties of Ferroelectric Perovskite Thin Films: Mechanisms of Dielectric and Photoelectrochemical Enhancement - Ghitiu, Ioan-Mihail; Nemnes, George Alexandru; Scarisoreanu, Nicu Doinel (Crystals (Basel), 2025)
Various types of strain, as well as chemical pressure induced by dopants, can effectively tailor the performance of perovskite thin films, including their optical, electrical or photoelectrochemical properties. The control of these functional properties through such engineering techniques is key to fulfilling the application-specific requirements of ferroelectric devices in various fields. Numerous models and experimental data have been published on this subject, especially on ferrite-based ferroelectric materials. Within this paper, the mechanisms of tuning ferroelectric intrinsic properties, such as polarization and ferroelectric domain configurations, through epitaxial strain and doping, as well as the role of these techniques in influencing functional properties such as dielectric and photoelectrochemical ones, are presented. This review examines the significant improvements in dielectric properties and photoelectrochemical efficiency achieved by the strategical control of key functionalities including dielectric losses, domain structures, charge separation and surface reactions in strained/doped ferroelectric thin films, highlighting the advancements and research progress made in this field in recent years.